2016
DOI: 10.1093/hmg/ddw366
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide quantitative trait loci mapping of the human cerebrospinal fluid proteome

Abstract: Cerebrospinal fluid (CSF) is virtually the only one accessible source of proteins derived from the central nervous system (CNS) of living humans and possibly reflects the pathophysiology of a variety of neuropsychiatric diseases. However, little is known regarding the genetic basis of variation in protein levels of human CSF. We examined CSF levels of 1,126 proteins in 133 subjects and performed a genome-wide association analysis of 514,227 single nucleotide polymorphisms (SNPs) to detect protein quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…We also observe variants associated with disease susceptibilities which include allergy and infection prominently in VvsK and VvsP comparisons, inflammation in PvsK and VvsP and neuropsychiatric conditions in VvsK. Variants associated with a cerebrospinal fluid biomarker (rs2228145, IL6R ) [36] differentiate Vata and Kapha in both cohorts. rs2228145 polymorphism in IL6R also influences the function of IL6-a pro and anti-inflammatory cytokine.…”
Section: Prakriti Associated Variants In Common and Complex Diseasesmentioning
confidence: 73%
“…We also observe variants associated with disease susceptibilities which include allergy and infection prominently in VvsK and VvsP comparisons, inflammation in PvsK and VvsP and neuropsychiatric conditions in VvsK. Variants associated with a cerebrospinal fluid biomarker (rs2228145, IL6R ) [36] differentiate Vata and Kapha in both cohorts. rs2228145 polymorphism in IL6R also influences the function of IL6-a pro and anti-inflammatory cytokine.…”
Section: Prakriti Associated Variants In Common and Complex Diseasesmentioning
confidence: 73%
“…Finally, we detected very strong and genome-wide significant association between markers in CHI3L1 and CSF levels of YKL-40, representing the only cis pQTL finding in our analyses. To the best of our knowledge, our study is the first bona fide GWAS for all three of these CSF biomarkers with the exception of two small (n = 133 and n = 265) CSF pQTL GWAS on YKL-40 in people of Asian descent 34 and a GWAS on NF-L in non-demented elderly from the the Alzheimer Disease Neuroimaging (ADNI) cohort 35 . Of note, the former study also identified strong and genome-wide significant cis pQTL effects at the CHI3L1 / YKL-40 locus, corroborating our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior publications have implicated genetic variants in CHI3L1 to represent cis pQTLs of YKL-40 levels in blood 37,41-43 (for more details see:https://www.ebi.ac.uk/gwas/genes/CHI3L1). However, to the best of our knowledge, only one prior study has investigated YKL-40 levels in the human CSF34 . Notwithstanding that study's relatively small sample size (n=133) and different ethnicity (Japanese), this GWAS, too, reported very pronounced cis pQTL effects of genetic variants in CHI3L1.…”
mentioning
confidence: 99%
“…Studies using aptamer‐, immunoassay‐, or mass‐spectrometry‐based proteomics have shown how changes in protein abundance can be associated with variants both in cis and in trans. Notably, such proteome‐wide screens of pQTL have been conducted in yeast, mice, maize, human cell lines, and primary cell lines . The recent developments in pQTL discovery and mapping suggest that these approaches can illuminate the role of common genetic variants lacking mechanistic links to disease .…”
Section: Understanding the Phenotypic Effects Of Variants In Genome‐wmentioning
confidence: 99%